2017
DOI: 10.1007/978-3-319-61615-5_5
|View full text |Cite
|
Sign up to set email alerts
|

Microplastic Pollution in Inland Waters Focusing on Asia

Abstract: The presence of microplastics in marine environment is increasingly reported and has been recognized as an issue of emerging concern that might adversely affect wildlife and cause potential risk to the health of marine ecosystems. In addition, preliminary works demonstrated that microplastics are ubiquitously present in many inland waters with concentrations comparable or higher than those observed in marine environments. Asia is the most populous continent in the world, and most Asian countries are under rapi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(60 citation statements)
references
References 65 publications
1
54
0
5
Order By: Relevance
“…Reddy et al [59]) and may exclude those in the submicron size ranges. The environmental occurrence and sources of MPs in freshwater matrices in an African, Asian, and European context are further discussed in Dris et al [51], Wu et al [60], Khan et al [61], respectively.…”
Section: Occurrence In Freshwater Systemsmentioning
confidence: 99%
“…Reddy et al [59]) and may exclude those in the submicron size ranges. The environmental occurrence and sources of MPs in freshwater matrices in an African, Asian, and European context are further discussed in Dris et al [51], Wu et al [60], Khan et al [61], respectively.…”
Section: Occurrence In Freshwater Systemsmentioning
confidence: 99%
“…To date, only a few studies have reported the occurrence of microplastics in freshwater as compared to marine environment [1,2]. However, different patterns of these studies can be perceived, particularly in rivers, where the research scopes depend on the obtainability of the environmental or biological matrices in a particular location, its seasonality (temporally) and also spatial distributions.…”
Section: Introductionmentioning
confidence: 99%
“…Asia is one of the leading regions for plastics production, accounting for nearly half of the world's production (Wu et al 2017). Accordingly, the input of plastic wastes from East Asia into the adjacent ocean was estimated as the highest in the world (Jambeck et al 2015).…”
Section: Environmental Fate and Risks Of Chemical Contaminantsmentioning
confidence: 99%